Temperature dependence of hard magnetic properties of FePd nanoparticles prepared by sonoelectrochemistry - Van, Nguyen Thi Thanh; Trung, Truong Thanh; Nam, Nguyen Hoang; Luong, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 28 No 1, 2012)
Abstract: Hard magnetic properties of magnetic nanoparticles FePd were investigated in dependence of temperature. Magnetic nanoparticles FePd were prepared from palladium acetate and iron acetate by sonoelectrochemistry, an useful technique to make metallic nanoparticles using ultrasound. Upon the annealing at 450°C to 650°C samples have ordered L1 0 structure and show hard magnetic properties with high coercivity up to 2.1 kOe at room temperature and increases to 2.43 kOe with decreasing temperature down to 2 K.